2013
DOI: 10.1055/s-0032-1329981
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Limited Joint Mobility and Foot Deformities with Neurological Examination in Patients with Diabetes

Abstract: The results of this study show discordance between biomechanical abnormalities and neuropathy depending on the diagnostic test used. Tests that assess large myelinated nerve fibers are associated with the presence of deformities. Abnormal sudomotor function test is associated with limited joint mobility and this test has a greater capacity for selecting patients at risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
2
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 10 publications
(11 reference statements)
0
1
2
1
Order By: Relevance
“…This finding is in line with the results of studies conducted in Mizan Tepi, Southwest Ethiopia (36.5%) [ 19 ] and Jordan 34% [ 23 ]. However, the findings of this study are lower than those of studies conducted in Kenya, Iraq, the United Kingdom, India, Spain, and China, which found an overall prevalence of foot deformity among diabetic patients were 46% [ 39 ], 46.7% [ 40 ], 44.5% [19], 40% [ 41 ], 60.2% [ 42 ] and 42% [ 43 ] respectively. This difference could be due to variations in the study populations, study design, and assessment methods.…”
Section: Discussioncontrasting
confidence: 85%
“…This finding is in line with the results of studies conducted in Mizan Tepi, Southwest Ethiopia (36.5%) [ 19 ] and Jordan 34% [ 23 ]. However, the findings of this study are lower than those of studies conducted in Kenya, Iraq, the United Kingdom, India, Spain, and China, which found an overall prevalence of foot deformity among diabetic patients were 46% [ 39 ], 46.7% [ 40 ], 44.5% [19], 40% [ 41 ], 60.2% [ 42 ] and 42% [ 43 ] respectively. This difference could be due to variations in the study populations, study design, and assessment methods.…”
Section: Discussioncontrasting
confidence: 85%
“…This finding is in line with the results of studies conducted in Mizan Tepi, Southwest Ethiopia (36.5%) [17], and Jordan 34% [18]. However, the findings of this study are lower than those of studies conducted in Kenya, Iraq, the United Kingdom, India, Spain, and China, which found an overall prevalence of foot deformity among diabetic patients were 46% [29], 46.7% [30], 44.5% [19] , 40% [31], 60.2% [32], and 42% [33] respectively. This difference could be due to variations in the ages of study participants, study design, and assessment methods, or to differences in the study populations.…”
Section: Discussioncontrasting
confidence: 67%
“…We, and others, have also previously shown that DPN, including early-stage DPN, can reduce quality of life even in the absence of pain [ 6 , 7 ]. Individuals with DPN are recognized to have sensorimotor deficits, including reduced proprioceptive sense [ 8 ], ankle mobility, range of motion [ 9 , 10 ], and muscle strength [ 11 ], leading to reduced balance [ 12 ], gait and mobility alterations [ 9 , 13 ], and increased risk of falls [ 14 ]. It is unclear, however, if these functional deficits in individuals with DPN are associated with, and responsible for, reduction in HRQoL.…”
Section: Introductionmentioning
confidence: 99%